CO2 adsorption on microporous metal–organic frameworks unravelled by high-resolution X-ray computed tomography - Diponker Karmoker; Jorge Martinez-Garcia; Damian Gwerder; Benjamin Fumey; Andreas Borgschulte; Philipp Schuetz (e-Journal of Nondestructive Testing)
The continuous increase in atmospheric carbon dioxide (CO2) concentration has triggered global warming and climate change. Strong policies and novel, cost-effective CO2 control methods have been developed to mitigate these issues over the last years. Metal-organic frameworks (MOFs) have emerged as one of the most rapidly advancing areas of research in chemistry, driven by advancements in synthesis, structure determination, interdisciplinary research, and broadening applications. MOFs porous materials demonstrate significant CO2 capture and conversion capabilities due to their tunable physical and chemical properties. Characterization of the MOF’s pore structure and its effect on CO2 adsorption are crucial to understanding the CO2 storage mechanisms and, thus, for optimal MOF design. This study uses X-ray computed tomography (XCT) to investigate non-destructively how CO2 is adsorbed on MOF’s particles. This contribution presents the characterization of the micron-scale pore structure of a single MOF particle. The collected imaging data is used to calculate the effective permeability along the MOF’s particle through numerical simulations. Findings reveal that the pore connectivity decreases with the particle penetration length, thus reducing the available surface area for adsorption. Additionally, the permeability near the particle surface is found to be 6.39 times higher than inside the particle. Potential CO2 location sites at the particle surfaces were also identified and visualized.